2009
DOI: 10.1111/j.1442-200x.2008.02787.x
|View full text |Cite
|
Sign up to set email alerts
|

How frequent is adenoid obstruction? Impact on the diagnostic approach

Abstract: Clinical assessment is crucial to evaluate chronic nasal obstruction. The lateral nasopharyngeal roentgenogram provides objective evaluation of the adenoid but its limitations should be considered. Nasal endoscopy may substitute for radiology but should be reserved for unusual cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 6 publications
(6 reference statements)
1
25
1
Order By: Relevance
“…In the authors' opinion, skull radiographies should never replace the FNE as the reference exam. Future studies should in fact, direct the goals to find out their usefulness as a screening test, as Bitar et al did [38].…”
Section: Item Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…In the authors' opinion, skull radiographies should never replace the FNE as the reference exam. Future studies should in fact, direct the goals to find out their usefulness as a screening test, as Bitar et al did [38].…”
Section: Item Studiesmentioning
confidence: 96%
“…Fibronasoendoscopy (FNE), on the other hand, constitutes one of the most important nasopharyngeal diagnostic methods [35][36][37][38]. It is tridimensional, allowing direct and dynamic visualization of the nasopharynx.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods to assess the adenoid size were described such as the posterior rhinoscopy with a laryngeal mirror and the radiological examination of the nasopharynx. Nowadays, nasal endoscopy is a well-known and diffuse method in routinely daily practice in evaluating a children; the fiberoptic examination of both nasal cavities and pharynx is the only way of examination that allows direct visualization of the districts of interest and enables the correct diagnosis [2,5,11,[16][17][18][19][20][21]. A prospective study performed by Wang et al in 180 children, confirmed that the size of the adenoid tissue, as shown at nasal endoscopy, correlated very well with the nasal obstruction complaints, as well as the condition of the nasopharyngeal orifice of the Eustachian tube significantly corresponded with the type of tympanogram.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal respiratory obstruction is a very common condition in children and it is often associated with adenoid hypertrophy (AH) [1,2].…”
Section: Introductionmentioning
confidence: 99%